Avaliação de genótipos de meloeiro quanto à resistência à mosca minadora - Oliveira, Frederico Inácio Costa de (2014)
The melon (Cucumis melo L.) is one of the most important vegetables in the world. Given its peculiarities, as its short cycle and staggered planting, pest control culture is prejudiced, being spent every year large amounts of pesticides to control the miner fly (Liriomyza sativae Blanchard) in melon, which, since 2000, appears as the key pest. The genetic control among the control measures is the ideal medium to circumvent the damage caused by this insect alternative. Thus, the aim of this work to evaluate a collection of Cucumis melo L. germplasm for resistance to miner fly (Liriomyza sativae); resistant accessions to identify and correlate the variables within and between experiments and field cage in field and cage were tested 58 melon genotypes for resistance to leaf miner, 49 accesses the Active Germplasm Bank of melon Embrapa Vegetables, five accessions of the Germplasm Bank of Cucurbits for the Brazilian Northeast and four commercial hybrids. The work was divided into two experiments: field and cage. The field experiment was conducted at the Experimental Station of Pacajus – CE, of the Embrapa Tropical Agroindustry (CNPAT), from December 2012 to February 2013 in a completely randomized design with two replications and six plants per plot. The experiment was conducted in cages in the Laboratories of Entomology and of Plant Breeding and Genetic Resources, in Fortaleza, during the period March 2013 to ammonium in a completely randomized design with six replications, each plant, subjective score based on infestation and number of mines per leaf - in the field: a portion of the following characteristics were evaluated and cage - number of mines per leaf chlorophyll content of leaves and colorimetry. Data were submitted to Kruskal-Wallis test. To determine the degree of relationship between variables, we calculated the Pearson correlation coefficient. The results revealed statistically significant differences among accessions for all variables. Genotypes 16, 48 and 51 showed favorable results for resistance in both experiments, so are best suited for future research focusing on improving introgression of resistance in melon L. sativae.